Growth pattern in Kabuki syndrome with a KMT2D mutation. Issue 12 (17th August 2016) - Schott, Dina A.; Blok, Marinus J.; Gerver, Willem J. M.; Devriendt, Koenraad; Zimmermann, Luc J. I.; Stumpel, Constance T. R. M.
Abstract : Kabuki syndrome is a multiple congenital malformation syndrome with a spectrum of clinical features including short stature. Since there is no growth data on Kabuki syndrome patients with a proven KMT2D gene mutation, further research on growth and growth patterns is indicated. Data for this growth study on subjects with Kabuki syndrome were collected from referring clinicians. Subjects were eligible for inclusion in the study if the following criteria were met: a genetically confirmed diagnosis of Kabuki syndrome and no current treatment with growth hormones or other drugs that could influence growth. We present a report on growth data (n = 39) in Kabuki syndrome patients. The data showed that postnatal growth retardation is a clinical feature in all cases. All Kabuki syndrome subjects showed a growth deflection during childhood and a diminution of the pubertal growth spurt. A genotype–phenotype correlation was not observed. Further research is required in order to determine whether a defect in the growth hormone/IGF‐I axis and estrogen receptor plays a role in the growth retardation. © 2016 Wiley Periodicals, Inc.